Nd : glass rod laser with an output energy of. (April 2016) - Shaykin, A.A.; Kuzmin, A.A.; Shaikin, I.A.; Burdonov, K.F.; Khazanov, E.A.
Abstract: The energy of two orthogonally polarised pulses injected into an available multistage amplifier based on neodymium phosphate glass rods was increased from 300 to (in both pulses). The second output pulse with an energy of will be used to pump an additional parametric amplifier of a petawatt laser.